Attractiveness of Picea pungens to the bark beetle species Ips amitinus (Eichh.) and Pityogenes chalcographus (L.) - E. Kula; R. Kajfosz; J. Polívka (Journal of Forest Science, 2013)
Only two cambioxylophagous species (Ips amitinus and Pityogenes chalcographus) were found on sections of Picea pungens and Picea abies that belong to economically important pests of Norway spruce. Representatives of the Isarthron sp. (Cerambycidae) were developed on the examined sections of both P. abies and P. pungens. The monitoring of attractiveness of the spruce species P. pungens and P. abies to cambioxylophages revealed that P. pungens was more intensively attacked by I. amitinus while P. chalcographus was more abundant on P. abies. Both bark beetle species preferred shaded parts of tree trunks, although their development was more successful on the sun-exposed side. On P. pungens, abundance of P. chalcographus decreased and abundance of I. amitinus increased with increasing trunk volume. Blue spruce was more attractive to Isarthron sp. compared to Norway spruce.